Review: Activation patterns of microglia and their identification in the human brain. Issue 1 (22nd January 2013) - Boche, D.; Perry, V. H.; Nicoll, J. A. R.
<x xml:space="preserve">Abstract</x> Microglia in the central nervous system are usually maintained in a quiescent state. When activated, they can perform many diverse functions which may be either beneficial or harmful depending on the situation. Although microglial activation may be accompanied by changes in morphology, morphological changes cannot accurately predict the function being undertaken by a microglial cell. Studies of peripheral macrophages and in vitro and animal studies of microglia have resulted in the definition of specific activation states: M1 (classical activation) and M2 (sometimes subdivided into alternative activation and acquired deactivation). Some authors have suggested that these might be an overlapping continuum of functions rather than discrete categories. In this review, we consider translational aspects of our knowledge of microglia: specifically, we discuss the question as to what extent different activation states of microglia exist in the human central nervous system, which tools can be used to identify them and emerging evidence for such changes in ageing and in Alzheimer's disease.